Impact of interaction term between education and loan size on women’s decision making - Yasmeen, Kausar; Abd Karim, Mohd Zaini (Macrothink Institute, 2014)
The purpose of this paper is to evaluate the impact of the microfinance involvement of women’s household decision making.The cross sectional data for this study is collected by using questionnaires.Using random sampling, 744 households are selected from female clients of Khushhali Bank and National Rural Support Program in Bahawalpur Division, Pakistan. We used the multinomial Logit and multinomial Probit model.The results show the woman's borrowers are more empower than women no borrowers.The coefficient of the loan size increases woman's household making empowerment. This paper is intended to be a valuable contribution in term of socio- economic and political arena.